Figurative Language on The Lyrics Of The Song by Mili In The Game Library of Ruina - Belliawan Pramudya (Universitas Nahdlatul Wathan Mataram, 2024)
This study observes the intricate realm of figurative language contained in the song lyrics of MILI, a Japanese music group known for their ethereal and emotive compositions, specifically within the context of the game